1997
DOI: 10.2466/pr0.1997.81.3.723
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Hope, Optimism, and Health

Abstract: The present investigation sought to distinguish hope from optimism in the context of a 10-wk. prospective study involving reports of health outcomes. Gottschalk's (1985) Hope Scale and Scheier and Carver's (1987) Life Orientation Test which assesses optimism were given to subjects, along with a health questionnaire. Ten weeks later subjects were given a second health questionnaire. To rule out potential confounds we included measures of neuroticism, depression, extroversion, and social desirability. After cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 26 publications
2
48
0
2
Order By: Relevance
“…21 Third, eliminating the risk of deportation and providing access to employment opportunities could raise hope and reduce psychosocial stress, which might directly improve mental health and indirectly affect physical health by leading to improved health behaviours. 22,23 Despite these strong theoretical links, the health consequences of the DACA programme have not yet been explored. More generally, studies linking policies targeting undocumented migrants to health outcomes are generally descriptive, with the underlying causality less clear.…”
Section: Introductionmentioning
confidence: 99%
“…21 Third, eliminating the risk of deportation and providing access to employment opportunities could raise hope and reduce psychosocial stress, which might directly improve mental health and indirectly affect physical health by leading to improved health behaviours. 22,23 Despite these strong theoretical links, the health consequences of the DACA programme have not yet been explored. More generally, studies linking policies targeting undocumented migrants to health outcomes are generally descriptive, with the underlying causality less clear.…”
Section: Introductionmentioning
confidence: 99%
“…These and others either emphasize the agency or the pathways, but not both equally as does hope. Studies have clearly shown that hope has discriminant validity among positive psychological constructs (Magaletta & Oliver, 1999;Scioli et al, 1997).…”
Section: Hope As the Most Unique Pob Capacitymentioning
confidence: 99%
“…Peterson & Luthans, 2003), and between Chinese factory workers' hope and their supervisor rated performance and merit salary . More generally, hope has been found to relate to performance in various domains, including academic and athletic achievement, physical and mental health, survival and coping beliefs and skills, and other desirable positive life and well-being outcomes (Curry, Snyder, Cook, Ruby, & Rehm, 1997;Kwon, 2000;Onwuegbuzie & Snyder, 2000;Range & Pentin, 1994;Scioli et al, 1997;Snyder, 2000). Theory building also continues to emerge regarding the performance impact of hope (Luthans, 2002a(Luthans, , 2002bLuthans, Youssef, et al, 2007a;Luthans & Youssef, 2004;Youssef & Luthans, 2003) and its cross-cultural applications Luthans, Van Wyk, & Walumbwa, 2004;Youssef & Luthans, 2006).…”
Section: Hope As a State-like Psychological Resource Capacitymentioning
confidence: 99%